Parathyroid Hormone Shifts Cell Fate of a Leptin Receptor‐Marked Stromal Population from Adipogenic to Osteoblastic Lineage. (2nd August 2019) - Yang, Mengyu; Arai, Atsushi; Udagawa, Nobuyuki; Zhao, Lijuan; Nishida, Daisuke; Murakami, Kohei; Hiraga, Toru; Takao‐Kawabata, Ryoko; Matsuo, Koichi; Komori, Toshihisa; Kobayashi, Yasuhiro; Takahashi, Naoyuki; et al.
ABSTRACT: Intermittent parathyroid hormone (iPTH) treatment induces bone anabolic effects that result in the recovery of osteoporotic bone loss. Human PTH is usually given to osteoporotic patients because it induces osteoblastogenesis. However, the mechanism by which PTH stimulates the expansion of stromal cell populations and their maturation toward the osteoblastic cell lineage has not be elucidated. Mouse genetic lineage tracing revealed that iPTH treatment induced osteoblastic differentiation of bone marrow (BM) mesenchymal stem and progenitor cells (MSPCs), which carried the leptin receptor (LepR)‐Cre. Although these findings suggested that part of the PTH‐induced bone anabolic action is exerted because of osteoblastic commitment of MSPCs, little is known about the in vivo mechanistic details of these processes. Here, we showed that LepR + MSPCs differentiated into type I collagen (Col1) + mature osteoblasts in response to iPTH treatment. Along with osteoblastogenesis, the number of Col1 + mature osteoblasts increased around the bone surface, although most of them were characterized as quiescent cells. However, the number of LepR‐Cre‐marked lineage cells in a proliferative state also increased in the vicinity of bone tissue after iPTH treatment. The expression levels of SP7 / osterix ( Osx ) and Col1, which are markers for osteoblasts, were also increased in the LepR + MSPCs population in response to iPTH treatment. In contrast, the expression levels of Cebpb, Pparg, and Zfp467, which are adipocyte markers, decreased in this population. Consistent with these results, iPTH treatment inhibited 5‐fluorouracil‐ or ovariectomy (OVX)‐induced LepR + MSPC‐derived adipogenesis in BM and increased LepR + MSPC‐derived osteoblasts, even under the adipocyte‐induced conditions. Treatment of OVX rats with iPTH significantly affected the osteoporotic bone tissue and expansion of the BM adipose tissue. These results indicated that iPTH treatment induced transient proliferation of the LepR + MSPCs and skewed their lineage differentiation from adipocytes toward osteoblasts, resulting in an expanded, quiescent, and mature osteoblast population. © 2019 American Society for Bone and Mineral Research.